Effects of instruction based on realistic mathematics education on mathematics achievement: A meta-analysis study Gerçekçi matematik eğitimi destekli öğretimin matematik başarısına etkisi: Bir meta-analiz çalışması - Kaplan, Abdullah; Duran, Murat; Doruk, Muhammet; Öztürk, Mesut (Journal of Human Sciences, 2015)
The purpose of this research is to determine the overall effect of instruction based on realistic mathematics education on mathematics achievement. The Meta-Analysis method recently increased in popularity in the field of educational science is used to accomplish this goal. Some criterions have been put in the determination of the study included in the survey and 12 national thesis in accordance with these criterions constituted the sample of this study. Process effectiveness method of meta-analysis is used in the analysis of data and Hedges’s g is used in the calculation of effect size of the study. At the end of the study, realistic mathematics education has an overall, positive and moderate effect on the mathematics achievement (Q = 16.406; p = 0.127). Howewer, the distribution of the effect sizes of the studies included in the survey are found to be homogeneous. At the end of the Z test carried out for the purpose of statistical significance, the value of effect size is observed statistically significant (Z = 7.966; p <0.05). The number of error protection is calculated 91 study to determine the publication bias of the study according to Orwin’s method. According to Orwin’s Fail Safe-N, the research could not have publication bias. Özet Bu araştırmanın amacı gerçekçi matematik eğitiminin matematik başarısı üzerindeki genel etkisini belirlemektir. Bu amacı gerçekleştirmek için eğitim bilimleri alanında yakın zamanda popülerliği artan meta-analiz yöntemi kullanılmıştır. Araştırmaya dâhil edilecek çalışmaların belirlenmesinde bazı kriterler belirlenmiş ve bu kriterlere uygun olan 12 ulusal tez bu araştırmanın örneklemini oluşturmuştur. Verilerin analizinde işlem etkililiği meta analizi yöntemi kullanılmış olup araştırmaların etki büyüklüklerinin hesaplanmasında Hedges’s g kullanılmıştır. Araştırma sonucunda gerçekçi matematik eğitiminin matematik başarısı üzerinde genel olarak, pozitif yönde ve orta düzeyde (Q= 16.406; p= 0.127) etkiye sahip olduğu ve araştırmaya dâhil edilen çalışmaların etki büyüklükleri dağılımının homojen olduğu görülmüştür. İstatistiksel anlamlılık amacıyla yapılan Z testi sonunda etki büyüklüğü değerinin istatistiksel olarak anlamlı olduğu görülmüştür (Z=7.966; p<0.05). Araştırmanın yayın yanlılığını test etmek amacıyla Orwin’in yöntemine göre hata koruma sayısı 91 hesaplanmıştır. Bulunan bu değere göre çalışmanın yayın yanlılığına sahip olmadığı söylenebilir.